2019
DOI: 10.31557/apjcp.2019.20.10.2965
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Women’s Knowledge and Attitude toward Cervical Cancer Screening, Treatment, and Prevention: A Cross-Sectional Study in Qassim Region (2018-2019)

Abstract: Background: Cervical cancer is a preventable and curable disease if early diagnosed; however, most of the cases present late; hence, there is a need to raise the awareness about cervical cancer and to establish screening programs. We aimed to assess the knowledge and attitudes toward screening and to determine the current status of awareness among women. Methods: We conducted a cross-sectional study among 2,220 Saudi women in the Qassim region using a validated questionnaire that gathers data on socio-demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 14 publications
8
36
0
Order By: Relevance
“…[ 30 ] Likewise, several studies in Saudi Arabia found unsatisfactory levels of knowledge pertaining to cervical cancer and screening. [ 3 24 25 26 27 30 31 32 33 34 ] All these results indicate the need for improvement in the levels of awareness about screening tools for cervical cancer. However, studies in Western countries showed better levels of knowledge of the Pap smear as a screening tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 30 ] Likewise, several studies in Saudi Arabia found unsatisfactory levels of knowledge pertaining to cervical cancer and screening. [ 3 24 25 26 27 30 31 32 33 34 ] All these results indicate the need for improvement in the levels of awareness about screening tools for cervical cancer. However, studies in Western countries showed better levels of knowledge of the Pap smear as a screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between educational academic year and age with knowledge scores on cervical cancer reflects the students' educational level. [ 16 17 29 32 33 34 ] Students with parents in the health profession also had increased scores. Nevertheless, monthly income did not significantly affect the knowledge scores.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding awareness level were measured in university students and the general population in Riyadh, Jeddah, Al-Ahsa, Hail, Qassim, and the southern region [16][17][18][19][20][21][22][23][24]. However, different results were obtained, suggesting that the knowledge level varies among women as a function of their occupation or region.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Similar results were also found in the study among Saudi women, whereby 70% of women had previous knowledge of CC, but had very low awareness that HPV was the main risk factor for CC (3.2%). 21 A study conducted in Ethiopia revealed only 30% of the participants had knowledge of CC. In comparison, our study showed that 40.1% of women attending gynaecological clinics in Kazakhstan were aware of CC and 25.7% were aware of the HPV infection as a risk factor for CC.…”
Section: Discussionmentioning
confidence: 99%